Fuzzy Evaluation of SWOT analysis - Haile, Meaza; Křupka, Jiří (My University, 2016)
To develop a strategy for an organization it is important to understand the organization and its surrounding environment. Strength, Weakness, Opportunity, Threat (SWOT) analysis is a famous tool to perform this task precisely by showing the strength, weakness of the organization and the external factors, opportunities and threats that affect its success. SWOT analysis is commonly used by business; however, non-profit organizations also use SWOT analysis for decision-making and strategy evaluation. The limitation of SWOT analysis is that it does not give weight for the factors and there is no quantified result from the analysis. The methods introduced in this paper are Sugeno lambda measure and Choquet fuzzy integral. Sugeno lambda measure is used for aggregating the importance of characteristics and Choquet fuzzy integral is used for the overall analytical evaluation of strength, weakness, opportunity and threat of a specific organization. The methods discussed in this paper provide a way to quantitatively evaluate SWOT analysis of an organization, without having to worry about dependencies among characteristics. A case study has been conducted for a currency exchange office and the region of Pardubice, Czech Republic (CR) to explain the application of the proposed approach for profit and non- profit organizations
Fuzzy hodnocení SWOT analýzy
Keywords: Choquet fuzzy integral; Fuzzy membership function; Strategy evaluation; Sugeno fuzzy integral; Sugeno λ-measure; SWOT analysis; Yager's ranking indices; Choquet fuzzy integral; funkce příslušnosti; strategiské hodnocení; Sugeno fuzzy integrál; Sugeno λ-míra; SWOT analýza; Yager's ranking indikátory